Breathing patterns of advanced pianists while executing four performing tasks - Nassrallah, Flora G (University of Ottawa (Canada), 2010)
Over the last fifty years, researchers have taken an interest in the breathing of different musicians. Little is known on the breathing patterns of pianists, however. Two main studies on the subject determined that a variation in meter affects breathing rhythms and that breathing rate might be linked to tempo and musical gestures, but we do not know whether a relationship exists between pianists' respiratory cycles and the movements they make when playing, or between breathing and specific musical elements such as rhythm, meter, tempo or phrasing. Eight pianists played the C major scale, the C major arpeggio, a Hanon five-finger exercise, the Minuet in G major by Petzold, and Fur Elise by Beethoven on a Yamaha Disklavier. During their performances, respiration was monitored by an inductive plethysmography system (RIPmate Respiratory Effort System). Although the results were not consistent across participants, it was clear that for some pianists breathing and performing were related.
Keywords: Health Sciences, Recreation.